Anode pole piece, secondary battery and electric equipment

By applying anode coating of transition metal inorganic substances on the anode material of lithium-ion batteries, the problem of lithium dendrites is solved, and the cycle stability and safety of the battery are improved.

CN119812208APending Publication Date: 2025-04-11ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411938768.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art cannot effectively solve the problem of lithium dendrites precipitation during the charging and discharging of anode materials in lithium-ion batteries, resulting in battery safety hazards and performance degradation.

Method used

An anode coating containing transition metal inorganic substances is used to promote uniform deposition and peeling of lithium ions through its uniform electric field distribution and high conductivity at the interface between the electrode and the electrolyte, thereby reducing the risk of lithium dendrites precipitation.

Benefits of technology

It significantly reduces the risk of lithium dendrites precipitation, improves the cycle stability and safety of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812208A_ABST
    Figure CN119812208A_ABST
Patent Text Reader

Abstract

The invention discloses an anode pole piece, a secondary battery and electric equipment, the anode pole piece comprises a current collector and an anode material layer formed on the surface of the current collector, the anode material layer is provided with an anode coating in a direction far away from the current collector, and the anode coating comprises a transition metal inorganic substance. According to the scheme, the anode coating containing the transition metal inorganic matter is arranged, in the initial circulation stage of the battery cell, after the functional coating is successfully converted, transition metal ions evenly distributed in the coating can effectively homogenize electric field distribution at the interface of an electrode and electrolyte, then the uniformity of lithium ion (Li < + >) flow is promoted, and the battery cell performance is improved. And the problems of local polarization and lithium precipitation caused by slow transmission rate of local lithium ions are relieved, so that the risk of lithium precipitation is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy technology, and in particular to an anode electrode sheet, a secondary battery and an electrical device. Background Art

[0002] During the battery charging process, the cathode (positive electrode) material undergoes lithium ion deintercalation reaction, while the anode (negative electrode) undergoes lithium ion intercalation reaction. Taking the SiC composite graphite negative electrode as an example, during normal charging, the negative electrode mainly undergoes two processes: one is the lithium intercalation reaction of graphite, that is, lithium ions are intercalated between graphite layers to form lithiated graphite; the other is the alloying reaction of Si, that is, silicon reacts with lithium ions to form silicon-lithium alloy. However, as the number of charge and discharge cycles increases, the electrolyte is gradually consumed, and the microstructure of the negative electrode material will also change, which will cause the polarization degree of the negative electrode lithium intercalation reaction to continue to intensify during the charging process, thereby causing the negative electrode potential to gradually decrease. When the local potential of the negative electrode drops to close to or below the precipitation potential of lithium metal, a lithium precipitation reaction will occur in this area, that is, lithium ions are directly reduced to lithium metal.

[0003] like Figure 1 As shown, the traditional negative electrode includes a current collector (Cu foil 1) and a SiC composite graphite material 2. During the cycle, lithium dendrites 3 are easily formed on the surface of the SiC composite graphite material. Since the lithium ion transfer rate inside the battery is different in different regions, those areas with slower lithium ion transfer rates will face greater polarization, making them more likely to become the preferred locations for lithium metal precipitation. This lithium precipitation reaction usually occurs on the electrode surface, and the precipitated lithium metal often exists in the form of dendrites. These lithium dendrites have high penetrability and can easily pierce the battery separator, thereby causing an internal short circuit in the battery, posing a major safety hazard to the battery cell.

[0004] More importantly, the formation of lithium dendrites is irreversible. During the subsequent discharge process, these lithium dendrites cannot be effectively stripped into lithium ions (Li + ) and re-embedded into the cathode material, resulting in a continuous decrease in the available capacity of the battery cell. In addition, lithium dendrites have a larger specific surface area and react more violently with the electrolyte, which accelerates the consumption of the electrolyte and further increases the performance degradation and failure risk of the battery cell.

[0005] In response to the problem of lithium deposition, some technical means have been taken to alleviate it, such as cathode corner drilling, cathode embossing and other processes, which aim to improve the uniformity of lithium ion transmission and reduce the degree of polarization. However, these methods cannot fundamentally solve the problem of lithium deposition. Once the lithium deposition reaction begins, lithium metal tends to precipitate directly on the anode surface, causing irreversible capacity loss. Therefore, in the future, more effective strategies still need to be explored to inhibit the lithium deposition reaction and ensure the safety and cycle stability of the battery. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides an anode pole piece that can reduce the risk of lithium deposition.

[0007] The present invention also provides a secondary battery containing the anode electrode sheet.

[0008] The present invention also provides an electric device with the secondary battery.

[0009] The anode electrode according to the first aspect of the present invention comprises a current collector and an anode material layer formed on the surface of the current collector, wherein the anode material layer is provided with an anode coating in a direction away from the current collector, and the anode coating comprises a transition metal inorganic substance.

[0010] The anode pole piece according to the embodiment of the present invention has at least the following beneficial effects: the scheme of the present invention provides an anode coating containing transition metal inorganic substances. In the initial cycle stage of the battery cell, after the functional coating is successfully converted, the transition metal ions uniformly distributed in the coating can effectively homogenize the electric field distribution at the interface between the electrode and the electrolyte, thereby promoting the uniformity of the lithium ion (Li+) flow, alleviating the local polarization phenomenon and lithium precipitation problem caused by the slow local lithium ion transmission rate, thereby reducing the risk of lithium precipitation. The transition metal ions with uniformly distributed electric fields in the coating effectively homogenize the electric field distribution at the interface between the electrode and the electrolyte through their unique charge distribution and electric field effect, thereby promoting the uniform deposition and stripping process of lithium ions. This feature is of great significance for alleviating local polarization, reducing the uneven distribution of lithium ions, and reducing the risk of lithium precipitation.

[0011] According to some embodiments of the present invention, the transition metal inorganic substance includes transition metal nitride and transition metal fluoride.

[0012] The coating cleverly combines two key components, transition metal fluorides and transition metal nitrides. Through their synergistic effect, the uniform distribution of the electric field and the smooth conduction of the lithium ion flow can be achieved, and the precipitation of lithium metal on the surface of the negative electrode material can be effectively inhibited. During the cyclic charge and discharge process of the battery cell, these components will undergo a gradual chemical reaction process and eventually transform into LiF (lithium fluoride), Li3N (lithium nitride) and the corresponding transition metal ions. This chemical reaction not only promotes the deep integration of the coating components, but also gives the coating unique physical and chemical properties. After this transformation process, the generated anode coating exhibits several significant advantages: First, it presents a highly uniform and dense structure. This structural feature ensures the effective transmission path of ions inside the coating, while reducing unnecessary voids and defects, and improving the overall stability and durability of the coating. Secondly, the coating exhibits excellent lithium ion conductivity, which is mainly due to the high conductivity of Li3N, which significantly accelerates the transmission rate of lithium ions at the interface between the electrode and the electrolyte, thereby optimizing the reaction kinetics of the battery cell. In addition, the introduction of LiF brings a higher Young's modulus to the coating, which means that the coating can maintain good shape stability and mechanical strength when subjected to external forces. This feature is crucial to reducing the volume change and structural damage of the electrode during charging and discharging, and also helps to inhibit the growth of lithium dendrites, further reducing the risk of internal short circuits and lithium precipitation caused by lithium dendrites piercing the separator.

[0013] In summary, the anode coating on the pole piece of the scheme of the present invention, with its excellent lithium ion conductivity, high Young's modulus and transition metal ion distribution characteristics that can effectively and evenly distribute the electric field, significantly reduces the risk of lithium dendrite precipitation in the battery cell during the cyclic charge and discharge process. These characteristics together lay a solid foundation for the stability of the overall performance of the battery cell and the extension of the cycle life.

[0014] In the initial cycle stage of the battery cell, after the functional coating is successfully converted, it will play the following key roles: ① The transition metal ions evenly distributed in the coating can effectively homogenize the electric field distribution at the interface between the electrode and the electrolyte, thereby promoting the uniformity of the lithium ion (Li+) flow, and alleviating the local polarization phenomenon and lithium precipitation problems caused by the slow local lithium ion transmission rate; ② Li3N, due to its extremely high lithium ion conductivity, can significantly accelerate the lithium ion transmission rate at the interface between the electrode and the electrolyte, improve the reaction kinetics of the battery cell, and thus reduce the risk of lithium precipitation caused by overall polarization; ③ LiF, with its high Young's modulus, can not only effectively reduce the structural damage caused by the change of electrode thickness during the charge and discharge cycle, but also effectively inhibit the growth of lithium dendrites, providing an important protective function to prevent lithium dendrites from piercing the diaphragm.

[0015] According to some embodiments of the present invention, the transition metal nitride includes at least one of MoN, TiN or CuN. The transition metal nitride can be + Oxidation-reduction reaction occurs to generate the corresponding transition metal element and Li3N, but it cannot react with Li + Other transition metal nitrides that undergo redox reactions are not within this range.

[0016] According to some embodiments of the present invention, the transition metal fluoride includes at least one of CuF2, FeF3 or AgF. The transition metal fluoride can be reacted with Li + Oxidation-reduction reaction occurs to generate the corresponding transition metal element and LiF, but it cannot react with Li + Other transition metal fluorides that undergo redox reactions are not within this scope.

[0017] According to some embodiments of the present invention, the anode coating further comprises a binder. The binder makes the transition metal inorganic material more evenly and densely distributed, and the uniform and dense structure of the coating effectively isolates the direct contact between the negative electrode material and the electrolyte, significantly reducing the side reactions between them, thereby greatly extending the cycle life of the battery cell while maintaining the same electrolyte retention amount.

[0018] According to some embodiments of the present invention, the binder includes at least one of PVDF (polyvinylidene fluoride), SBR (emulsion styrene butadiene rubber), CMC (carboxymethyl cellulose), PAA (polyaryl acetylene), PAN (polyacrylonitrile) or PTFE (polytetrafluoroethylene). The binder is an oil-based or water-based binder commonly used in lithium-ion batteries.

[0019] According to some embodiments of the present invention, the anode coating comprises a transition metal nitride, a transition metal fluoride and a binder, wherein the total mass of the transition metal nitride, the transition metal fluoride and the binder is m, the ratio of the weight of the transition metal nitride to m is W1, the ratio of the weight of the transition metal fluoride to m is W2, the ratio of the weight of the binder to m is W3, W1+W2+W3=100%, 40%≤W1 / (W1+W2)≤70%. The ratio of the transition metal compound to the transition metal fluoride is precisely controlled to better improve the ionic conductivity and Young's modulus of the composite layer at the same time, thereby improving the overall performance of the battery cell.

[0020] According to some embodiments of the present invention, W1 and W2 satisfy the following relationship: 40% ≤ W1 / (W1+W2) ≤ 70%. When W1 and W2 satisfy the above relationship, after the functional material is converted into a functional coating in which LiF, Li3N and metal particles are uniformly mixed, its lithium ion transmission rate N and Young's modulus M are both at a high level. If the value of W1 continues to increase, the Young's modulus M will decrease; on the contrary, if the value of W2 increases further, the lithium ion conductivity N will decrease. Therefore, when W1 and W2 are selected to be within this specific interval, the performance of the functional coating reaches the optimal state.

[0021] According to some embodiments of the present invention, 3 / 7≤W2 / W1≤6 / 4, such as 4 / 6, 5 / 5, etc.

[0022] According to some embodiments of the present invention, the value range of W3 satisfies the following condition: 0.1%≤W3≤10%. For example, it is 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8% or 9%. By precisely controlling the content ratio of the binder, the uniform Li-ion transition metal nitride and transition metal fluoride in the coating can be effectively promoted. + The induction of current can significantly improve the Young's modulus of the coating and enhance its physical stability. This regulation strategy not only optimizes the ion transport path inside the coating, but also ensures that the binder can firmly bond the coating material to form a stable and reliable structural connection. As a result, the battery cell can maintain better performance stability during the charge and discharge cycle, reducing the risk of performance degradation caused by the unstable coating structure, thereby synergistically improving the overall performance and service life of the battery cell.

[0023] According to some embodiments of the present invention, the value range of W3 satisfies the following condition: 1%≤W3≤10%.

[0024] According to some embodiments of the present invention, the ionic conductivity of the anode coating is N, and the Young's modulus of the functional coating is M, wherein M, N, W1 and W2 need to satisfy the following relationships respectively: M = (-55*W1 / (W1+W2)+65)*(W1+W2), N = (5.9997*10 -3 *W1 / (W1+W2)+3*10 -7 )*(W1+W2). (Without considering the influence of the adhesive, based on the ionic conductivity of pure Li3N (6*10 -3 Scm -1 ) and Young's modulus (10MPa), and pure LiF ion conductivity (3*10 - 7 Scm -1) and Young's modulus (65MPa) are linearly fitted to obtain the approximate curve: M0 = -55*W1 / (W1+W2)+65, N0 = 5.9997*10 -3 *W1 / (W1+W2)+3*10 -7 ; Considering that the higher W3 is, that is, the lower W1+W2 is, the lower M and N will be, so we continue to introduce the influence of (W1+W2) on M and N).

[0025] According to some embodiments of the present invention, N≥0.0023S / cm, M≥25.9Gpa. The coating of the present invention has excellent lithium ion conductivity and high Young's modulus. The high level of lithium ion conductivity significantly accelerates the transfer rate of lithium ions at the interface between the electrode and the electrolyte, thereby optimizing the reaction kinetics of the battery cell. A higher Young's modulus means that the coating can maintain good shape stability and mechanical strength when subjected to external forces. This property is crucial to reducing the volume change and structural damage of the electrode during charging and discharging, and also helps to inhibit the growth of lithium dendrites, further reducing the risk of internal short circuits and lithium precipitation caused by lithium dendrites piercing the diaphragm.

[0026] According to some embodiments of the present invention, the thickness of the coating is T μm, and the thickness of the coating satisfies the following relationship: 0.045≤T≤1. The coating thickness is controlled within an appropriate range, which effectively improves the uniformity and efficiency of the coating in lithium ion transmission while ensuring that the first efficiency (i.e., initial efficiency) and energy density (ED) of the battery cell are not damaged.

[0027] According to some embodiments of the invention, 0.1≤T≤1.

[0028] According to some embodiments of the invention, 0.05(W1+W2)≤T≤10W3.

[0029] According to some embodiments of the present invention, the anode material layer comprises an anode active material, and the anode active material comprises at least one of a SiC composite graphite material, a Si / C composite material, and a SiO / C composite material.

[0030] According to the second aspect of the present invention, a secondary battery comprises the above-mentioned anode electrode sheet.

[0031] According to some embodiments of the present invention, the secondary battery further includes a cathode sheet and a separator, the cathode sheet and the anode sheet are wound or stacked, and the separator is disposed between the cathode sheet and the anode sheet.

[0032] According to the third aspect of the present invention, an electric device includes the secondary battery.

[0033] According to some embodiments of the present invention, the electrical device further includes a load, and the secondary battery is electrically connected to the load.

[0034] Since the secondary battery and the electrical equipment of the present invention have the same technical features as the anode electrode sheet described in any of the above items and can achieve the same technical effects, they will not be described in detail here.

[0035] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0037] Figure 1 This is a schematic diagram of the lithium-silicon-carbon negative electrode structure in the prior art.

[0038] Figure 2 Schematic diagram of the working principle of the anode electrode in an embodiment of the present invention.

[0039] Figure 3 Graph showing the variation of ionic conductivity and Young's modulus with W1 value in Example 1 of the present invention.

[0040] Figure numerals: 1. Cu foil; 2. SiC composite graphite material; 3. Lithium dendrite; 4. Lithium ion flow; 5. Anode coating; 6. Electric field. DETAILED DESCRIPTION

[0041] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be reagents and materials obtained from commercial channels. Unless otherwise specified, the same parameter in each embodiment has the same value. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limitations on the present invention.

[0042] In the description of the present invention, the description with reference to the term "some embodiments" or the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0043] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0044] Example 1

[0045] This example provides an anode pole piece, which includes a current collector (Cu foil 1), an anode material layer (SiC composite graphite material 2) and an anode coating 4 in sequence.

[0046] The preparation method of the anode coating is as follows:

[0047] S1. Prepare the functional material into a slurry, wherein the functional material is specifically: transition metal nitride, with a weight ratio of W1, specifically MoN; transition metal fluoride, with a weight ratio of W2, specifically CuF2; binder, with a weight ratio of W3, specifically PVDF, and solvent is NMP. W1+W2=98%,W1:W2=6:4, that is, W1 is 58.8%, W2 is 39.2%, and W3 is 2%.

[0048] S2. The slurry prepared by the above operation is evenly coated on the anode material layer. The coating thickness is T μm, where T is 0.1.

[0049] The working principle of the anode plate is as follows Figure 2 During the operation of the anode electrode, the anode coating 4 has the following functions: 1) uniform lithium ion flow 5; 2) uniform electric field 6; 3) increase Young's modulus; 4) increase compactness.

[0050] The ionic conductivity of the anode coating is N, and the Young's modulus of the functional coating is M. According to M = (-55*W1 / (W1+W2)+65)*(W1+W2), N = (5.9997*10 -3 *W1 / (W1+W2)+3*10 -7 )*(W1+W2), we can calculate that N≥0.0023S / cm, M≥25.9GPa. When W3 is fixed at 2%, the relationship between M, N and W1 is as follows Figure 3As shown. When W1 changes, W2 only needs to satisfy the relationship of W1+W2=98%,W3=2%,and 40%≤W1 / (W1+W2)≤70%, and can change within this range. Figure 3 It can be seen that as W1 / (W1+W2) increases, the ionic conductivity N increases and the Young's modulus M decreases. When W1=0, W1 / (W1+W2)=0, the ionic conductivity N reaches the minimum value of 2.94*10 -7 , the Young's modulus M value reaches a maximum of 63.7MPa (at this time, the ionic conductivity and Young's modulus are the values ​​of pure LiF, metal element and 2% adhesive mixed); similarly, when W2=0, W1 / (W1+W2)=1, and the N value reaches a maximum of 5.88*10 -3 , M reaches a minimum value of 9.8MPa (at this time, the ionic conductivity and Young's modulus are the values ​​of pure Li3N, metal element and 2% binder mixed together). The reason why the values ​​of N and M need to be within this range is that further reduction of N will seriously affect the transmission of lithium ions at the interface, affect the reaction kinetics of the battery cell, and deteriorate the electrochemical performance; and further reduction of the M value will greatly reduce the physical properties of the protective layer, making the protective layer more easily broken, and also deteriorating the cycle performance of the battery cell.

[0051] This example also provides a secondary battery, including the above-mentioned anode plate, a separator, an electrolyte and a cathode plate, the separator is located between the anode plate and the cathode plate, and the electrolyte is filled in the anode plate and the cathode plate.

[0052] This example also provides an electrical device, including a load and the above-mentioned secondary battery, wherein the secondary battery is used to provide electrical energy to the load.

[0053] Example 2

[0054] This example provides an anode electrode plate, a secondary battery and an electrical device, which differ from Example 1 in that: in the raw materials for preparing the anode coating, W1:W2=4:6, that is, W1 is 39.2% and W2 is 58.8%.

[0055] Example 3

[0056] This example provides an anode electrode sheet, a secondary battery and an electrical device, which differ from Example 1 in that: in the raw materials for preparing the anode coating, W1:W2=7:3, that is, W1 is 68.6% and W2 is 29.4%.

[0057] Example 4

[0058] This example provides an anode electrode plate, a secondary battery and an electrical device, which differ from Example 1 in that: in the raw materials for preparing the anode coating, W1+W2=99%, that is, W1 is 59.4%, W2 is 39.6%, and W3 is 1%.

[0059] Example 5

[0060] This example provides an anode electrode plate, a secondary battery and an electrical device, which differ from Example 1 in that: in the raw materials for preparing the anode coating, W1+W2=90%, that is, W1 is 54%, W2 is 36%, and W3 is 10%.

[0061] Example 6

[0062] This example provides an anode electrode plate, a secondary battery and an electrical device, which are different from Example 1 in that T is 1.

[0063] Example 7

[0064] This example provides an anode electrode plate, a secondary battery and an electrical device, which are different from Example 1 in that T is 2.

[0065] Example 8

[0066] This example provides an anode electrode sheet, a secondary battery and an electrical device, which are different from Example 1 in that T is 0.02.

[0067] Example 9

[0068] This example provides an anode electrode sheet, a secondary battery and an electrical device, which differ from Example 1 in that: in the raw materials for preparing the anode coating, W1:W2=1:9, that is, W1=9.8%, and W2 is 88.2%.

[0069] Example 10

[0070] This example provides an anode electrode sheet, a secondary battery and an electrical device, which differ from Example 1 in that: in the raw materials for preparing the anode coating, W1:W2=9:1, that is, W1=88.2%, and W2 is 9.8%.

[0071] Embodiment 11

[0072] This example provides an anode electrode plate, a secondary battery and an electrical device, which differ from Example 1 in that: in the raw materials for preparing the anode coating, W1+W2=99.8%, W1:W2=6:4, W1 is 59.88%, W2 is 39.92%, and W3 is 0.2%.

[0073] Example 12

[0074] This example provides an anode electrode plate, a secondary battery and an electrical device, which differ from Example 1 in that: in the raw materials for preparing the anode coating, W1+W2=60%, W1:W2=6:4, W1 is 36%, W2 is 24%, and W3 is 40%.

[0075] Comparative Example 1

[0076] This example provides an anode electrode sheet and a secondary battery, which differ from the anode electrode sheet in Example 1 in that the surface of the anode material layer does not contain an anode coating.

[0077] For the convenience of comparison, the parameters such as T value, transition metal nitride, transition metal fluoride and PVDF content in the embodiments and comparative examples are summarized as shown in Table 1:

[0078] Table 1

[0079]

[0080]

[0081] Performance test: The cathode material, electrolyte, diaphragm and other components are controlled to be the same, and the anode plates in the embodiment and the comparative example are respectively taken to assemble into soft-pack batteries. The energy density (ED) is tested at 25°C, and a 3.6C (1C=6.5A) rate charge and discharge cycle test is performed. After 800 cycles, the capacity retention rate and thickness change rate of the battery cell are tested.

[0082] The test results are shown in Table 2 below.

[0083] Table 2

[0084] Group ED(Wh / kg) Capacity retention rate Thickness change rate Example 1 820 83.00% 13.00% Example 2 820 82.80% 13.30% Example 3 820 82.50% 13.60% Example 4 820 82.10% 14.00% Example 5 820 81.80% 14.40% Example 6 815 82.90% 13.20% Example 7 790 80% 18% Example 8 821 71% 22% Example 9 820 75% 20% Example 10 820 81% 15% Embodiment 11 820 81.50% 14.80% Example 12 820 78% 19% Comparative Example 1 822 68% 25%

[0085] The data in Table 2 are analyzed as follows:

[0086] 1) Compared with Example 1 (W1:W2 ratio is 6:4), the content of transition metal nitride in Example 2 (W1:W2 ratio is 4:6) is reduced, while the content of transition metal fluoride is increased accordingly. This change reduces the content of Li3N in the protective layer and increases the content of LiF. Therefore, the lithium ion conductivity of the protective layer decreases, and the reaction kinetics of the battery cell also weakens, thereby reducing the electrochemical performance, but it is still at a better level than the prior art.

[0087] 2) Compared with Example 1, the Li3N content in Example 3 (W1:W2 ratio is 7:3) is significantly increased, which promotes the improvement of lithium ion transmission rate. However, this change also reduces the mechanical strength of the protective layer. As the number of battery cycles increases, the protective layer structure may suffer partial damage, resulting in a decrease in the overall performance of the battery cell, but it is still at a better level than the prior art.

[0088] 3) Example 4 is different from Example 1 in that the sum of W1 and W2 (i.e., W1+W2=99%) results in a reduction in the binder content. This change reduces the overall structural stability of the protective layer. Therefore, as the number of battery cycles increases, the capacity retention rate decreases and the expansion of the battery cell increases, but it is still at a relatively good level compared to the prior art.

[0089] 4) Example 5 (W1+W2=90%) Compared with Example 1, the binder content is significantly increased, which will reduce the ionic conductivity and Young's modulus at the same time, so the improvement effect is weakened, but it is still at a better level compared with the existing technology.

[0090] 5) Compared with Example 1, the coating thickness of Example 6 is increased, which in turn increases the thickness of the entire battery cell. This change leads to a decrease in the energy density (ED) of the battery cell and a slight deterioration in the cycle stability, but it is still at a relatively good level compared to the prior art.

[0091] 6) Compared with Example 1, the thickness of the functional anode coating in Example 7 is significantly increased, which also leads to an increase in the overall thickness of the battery cell and a decrease in energy density. In addition, the thicker functional anode coating increases the contact resistance, thereby slowing down the reaction kinetics inside the battery cell, resulting in a decrease in cycle performance, but it is still at a better level than the prior art.

[0092] 7) Compared with Example 1, Example 8 significantly reduces the thickness of the functional anode coating. Although the energy density is increased, the cycle stability of the battery cell is affected and reduced due to incomplete modification of the functional anode coating. However, it is still at a relatively good level compared with the existing technology.

[0093] 8) In Example 9, compared with Example 1, the content of transition metal fluoride is dominant, resulting in a decrease in the ionic conductivity of the functional anode coating. Although the mechanical strength has increased, the cycle stability of the battery cell still shows a downward trend, but it is still at a better level than the prior art.

[0094] 9) Example 10 Compared with Example 1, the transition metal nitride occupies a dominant position, which significantly increases the ionic conductivity of the entire functional anode coating. However, the mechanical strength is relatively weak, and the coating structure is easily damaged after cycling, which also leads to a decrease in cycle stability, but it is still at a better level than the prior art.

[0095] 10) Compared with Example 1, Example 11 further increases the content of functional substances in the functional anode coating, while significantly reducing the content of binder. This change leads to a decrease in the adhesion performance of the coating, which has an adverse effect on the cycle performance of the battery cell, specifically manifested in a decrease in the cycle capacity retention rate and an increase in the thickness expansion rate, but it is still at a relatively good level compared to the prior art.

[0096] 11) Compared with Example 1, Example 12 reduces the content of functional substances, resulting in a weakened effect of uniform lithium ion flow, and a significant reduction in Young's modulus. These changes also have an adverse effect on the cycle performance of the battery cell, causing the cycle performance to decline, but it is still at a relatively good level compared to the prior art.

[0097] 12) Compared with Example 1, Comparative Example 1 does not have a functional anode coating, and lithium plating is more serious, so the cycle capacity retention rate and expansion are significantly deteriorated.

[0098] In summary, the solution of the embodiment of the present invention significantly reduces the risk of lithium plating and significantly improves the cycle stability of the battery by providing the functional anode coating of the solution of the present invention. In addition, the adjustment of the composition ratio, content and the change of the coating thickness will have a certain impact on the composition of the protective layer, lithium ion conductivity, mechanical strength and the overall electrochemical performance (including energy density and cycle stability) of the battery cell.

[0099] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. An anode electrode sheet, comprising a current collector and an anode material layer formed on the surface of the current collector, wherein the anode material layer is provided with an anode coating in a direction away from the current collector, characterized in that: The anode coating comprises a transition metal inorganic substance.

2. The anode electrode according to claim 1, characterized in that: The transition metal inorganic substance includes transition metal nitride and transition metal fluoride; preferably, the transition metal nitride includes at least one of MoN, TiN or CuN; and / or, the transition metal fluoride includes at least one of CuF2, FeF3 or AgF.

3. The anode electrode according to claim 2, characterized in that: The anode coating further comprises a binder; preferably, the binder comprises at least one of PVDF, SBR, CMC, PAA, PAN or PTFE.

4. The anode electrode according to claim 3, characterized in that: The anode coating comprises a transition metal nitride, a transition metal fluoride and a binder, wherein the total mass of the transition metal nitride, the transition metal fluoride and the binder is m, the ratio of the weight of the transition metal nitride to m is W1, the ratio of the weight of the transition metal fluoride to m is W2, the ratio of the weight of the binder to m is W3, W1+W2+W3=100%, 40%≤W1 / (W1+W2); preferably, W1 and W2 satisfy the following relationship: 40%≤W1 / (W1+W2)≤70%.

5. The anode electrode according to claim 4, characterized in that: The ionic conductivity of the anode coating is N, and the Young's modulus of the functional coating is M, wherein M=(-55*W1 / (W1+W2)+65)*(W1+W2), N=(5.9997*10 -3 *W1 / (W1+W2)+3*10 -7 )*(W1+W2); preferably, N≥0.0023S / cm, M≥25.9Gpa.

6. The anode electrode according to claim 4, characterized in that: 3 / 7≤W2 / W1≤6 / 4; and / or, the value range of W3 satisfies the following condition: 0.2%≤W3≤10%.

7. The anode electrode according to any one of claims 1 to 6, characterized in that: The thickness of the positive coating is T μm, and the thickness of the positive coating satisfies the following relationship: 0.05≤T≤1.5; preferably, 0.1≤T≤1; more preferably, 0.005(W1+W2)≤T≤W3.

8. The anode electrode according to claim 1, characterized in that: The anode material layer contains an anode active material, and the anode active material includes at least one of a SiC composite graphite material, a Si / C composite material, and a SiO / C composite material.

9. A secondary battery, characterized in that: The secondary battery comprises the anode electrode sheet according to any one of claims 1 to 8.

10. An electrical equipment, characterized in that: The electric device comprises the secondary battery as claimed in claim 9.

Citation Information

Patent Citations

  • Interface protection structure, preparation method and battery comprising structure

    CN109728249A

  • Preparation method of lithium metal negative electrode and lithium metal negative electrode

    CN113299886A

  • Anode plate of lithium ion battery and application of anode plate

    CN115133030A

  • Lithium alloy containing Li3N / LiF and electrode and battery thereof

    CN115233062A

  • Composite negative electrode layer, preparation method and application of composite negative electrode layer in battery

    CN117525339A